Looking for Appropriate Forms of Intergovernmental Transfers for Municipalities in Transition Economies - Chang Woon Nam; Rüdiger Parsche (Center for Economic Studies and ifo Institute (CESifo), 2001)
Intergovernmental transfers can be either conditional or unconditional with regard to the autonomy of local governments in spending such financial means. Although fiscal decentralisation has recently been quite pronounced in Eastern European transition countries, the dominance of a purpose- and project-oriented, down-flow transfer system is apparent. In the context of unification, the west German municipal resource allocation system was also implemented in the eastern part of the country, which provides primarily unconditional transfers for local governments. Furthermore, in the case of adopting the principle of parallel development of fiscal capacity between the state and municipalities, as Saxony already has done, the intergovernmental transfer ratio is no longer exogenously but endogenously determined, which better guarantees a just resource allocation between the two jurisdictions. Since the subsidiarity principle backed by sufficient own fiscal resources and unconditional transfers appears to gain significance in providing local utilities, this study shows the recent Saxon experience with the unconditional transfers, which can be considered for the future fiscal devolution process of Eastern European transition countries.
Keywords: 330; intergovernmental transfers; fiscal decentralisation; local expenditure needs; municipal tax revenues; vertical fiscal equalisation; Saxony; Germany; European transition economies